Chemical constituents of dysoxylum acutangulum miq. and their bioactivities - Mohd Lazim, Mohd Izwan (2012)
A phytochemical studies on Dysoxylum acutangulum leaves have been carried out and resulted in the isolation of seven compounds including two new compounds assigned as chrotacumine E (62) and F (63), along with four known compounds; rohitukine (10), noreugenin (38), β-sitosterol (60), hexadecanoic acid (61) and one unsolved compound, Chrotacumine G (59). The structures of the compounds including their relative configurations were elucidated based on the spectroscopic data including Nuclear Magnetic Resonance (NMR), Gas Chromatography-Mass Spectrometry (GC-MS), Fourier Transform Infrared (FT-IR), Circular Dichorism (CD) and also by comparison with the previous reported works. Dysoxylum has been the subject of research interest in the field of natural products due to their unique chemistry and biological properties. Dysoxylum acutangulum are among those known to be used as traditional medicines. From the early investigations on these plants, some interesting new compounds were discovered,some of which exhibited noteworthy biological properties such as anti-tumor promoting, anti-acetylcholinesterase and ichthyotoxic activities. Screening for biological activities is an important preliminary step in natural products research when aiming at discovering bioactive compounds from plant. In this research, two extraction methods have been done which is liquid-liquid partition and acid base extraction to obtain alkaloidal extract. All extract was subjected to column chromatography silica gel to fractionate and purify. Based on a bioautographic Thin Layer Chromatography (TLC) profile of antiacetylcholinesterase activity on the major fractions of D. acutangulum leaves, hexane fraction has showed a promising activity. The most active hexane subfraction was further fractionated and purified by a bioassay-guided fractionation wherein hexadecanoic acid (61) was obtained showing as a potent acetylcholinesterase (AChE) inhibitor. On the contrary, the AChE activity of 61 was not significant (1mg/mL) when tested by Ellman’s method. In the ichthyotoxic assay carried out on Zebra fish (Denio rerio), EtOAc fraction was found to possess significant ichthyotoxicity compared to other fractions; hexane, BuOH, CHCl3 and aqueous. Meanwhile, BuOH fraction showed 70% inhibition in the tyrosinase assay. All of the isolated compounds were tested for their ichthyotoxicity, anti-acetylcholinesterase and anti-tyrosinase activity. However, none of them showed any significant activities.